Fragment-Based Discovery of 8-Hydroxyquinoline Inhibitors of the HIV-1 Integrase-LEDGF/p75 Interaction - Serrao, Erik (J Med Chem, 2013)
On the basis of an initial molecular modeling study suggesting the favorable binding of the “privileged” fragment 8-hydroxyquinoline with IN at the IN-LEDGF/p75 interface, we developed a set of modified 8-hydroxyquinoline fragments demonstrating micromolar IC(50) values for inhibition of the IN-LEDGF/p75 interaction, but significant cytotoxicity was associated with these initial compounds. Diverse modifications at the C5 and C7 carbons of the 8-hydroxyquinoline core improved potency, but reduction of diversity to only modifications at the C5 position ultimately yielded potent inhibitors with low cytotoxicity. Two of these particular compounds, 5-((p-tolylamino)methyl)quinolin-8-ol and 5-(((3,4-dimethylphenyl)amino)methyl)quinolin-8-ol, inhibited viral replication in MT-4 cells with low micromolar EC(50). This is the first study providing evidence for 8-hydroxyquinolines as novel inhibitors of the IN-LEDGF/p75 interaction. Our lead compounds are drug-like, have low molecular weights, and are amenable to various substitutions suitable for enhancing their potency and selectivity.